Politeness Strategies and Power Relations Depicted in Shark Tank Pitch Discourse - Muhammad Nur Assyddyq; Listya Arum Ridhawati (Lexicon, 2026)
This study analyzes politeness strategies and power asymmetry in entrepreneurial investment pitches by qualitative discourse analysis of 10 complete Shark Tank interactions (Seasons 12–16). Brown and Levinson (1987) politeness theory, refined by Fathi (2024), and Fairclough (2015) critical discourse analysis are applied to seven deal-successful and three no-deal pitches at the investment request, investor critique, and negotiation or rejection stages. The investigation found that deal-successful entrepreneurs used a range of strategies across three phases, while no-deal entrepreneurs relied on a single strategy under investor pressure. The use of topic control, interrogative sequencing, and evaluative reformulation consistently reinforced power imbalances, but individual instances imply that this power is created through interaction rather than predetermined by structure. Overall, the findings indicate that strategic flexibility—not specific politeness choices—is key for effective discourse management in high-stakes investment pitches, and that sociolinguistic analysis can reveal important communication patterns that outcome-focused studies have yet to examine systematically.